The Pharmacogenomic HLA Biomarker Associated to Adverse Abacavir Reactions: Comparative Analysis of Different Genotyping Methods - Stocchi, Laura; Cascella, Raffaella; Zampatti, Stefania; Pirazzoli, Antonella; Novelli, Giuseppe; Giardina, Emiliano (Current Genomics, 2012)
Many pharmacogenomic biomarkers (PGBM) were identified and translated into clinical practice, affecting the usage of drugs via label updates. In this context, abacavir is one of the most brilliant examples of pharmacogenetic studies translated into clinical practice. Pharmacogenetic studies have revealed that abacavir HSRs are highly associated with the major histocompatibility complex class I. Large studies established the effectiveness of prospective HLA-B*57:01 screening to prevent HSRs to abacavir. Accordingly to these results the abacavir label has been modified: the European Medicines Agency (EMA) and the FDA recommend/suggested that the administration of abacavir must be preceded by a specific genotyping test. The HLA locus is extremely polymorphic, exhibiting many closely related alleles, making it difficult to discriminate HLA-B*57:01 from other related alleles, and a number of different molecular techniques have been developed recently to detect the presence of HLA-B*57:01. In this review, we provide a summary of the available techniques used by laboratories to genotype HLA-B*57:01, outlining the scientific and pharmacoeconomics pros and cons.
Keywords: Comparative Analysis